The Effect of Outdoor Study-Based Experiential Learning Model on the Collaborative Ability of High School Geography Students - Anggraeni, Defita Dwi; Astutik, Sri; Pangastuti, Era Iswara; Susiati, Ana; Noviantoro, Kurnia Maulidi (Universitas Pendidikan Ganesha, 2025)
Conventional learning models have proven to be less than optimal, so a solution is needed using the Experiential Learning model with the outdoor study method. The purpose of this study is to examine the effect of the outdoor study-based Experiential Learning model on the collaboration abilities of high school geography students. This type of research is quantitative research using the Quasi Experiment method and uses the Post Test Only Control Group Design. This study takes and uses data to measure students' collaboration abilities by giving a collaboration questionnaire. The results of the study obtained an average score in the control class of 41 and an average score in the experimental class of 86 with the highest indicator of cooperation. This is influenced by good coordination from students. The data is strengthened by the results of the Independent Simple T-test using the collaboration ability value with a Sig. (2-Tailed) result of 0.000.